Información y computación en Fodor. - Blanco Salgueiro, Antonio (Anales del Seminario de Historia de la Filosofía, 2000)
The aim of this work is to assess Jerry Fodor's current project of combining an informational semantics for the language of thought and a computational theory of mental processes. First, a central notion in Fodoffs work is examined: the notion of "mechanism". Then, it is argued that, at least for the so called "Frege-cases", Fodor's account in The Blm and rhe Expert (1994) is not convincing.
Keywords: informational semantics; computation; mechanism; psycho logical explanation